2020
DOI: 10.1039/c9sc04849a
|View full text |Cite
|
Sign up to set email alerts
|

Readily accessible sp3-rich cyclic hydrazine frameworks exploiting nitrogen fluxionality

Abstract: A high yielding, flexible strategy to hydrazine based chemical libraries is reported. Using a single stereogenic center, good shape diversity and three dimensionality is achieved by exploitation of the fluxional behavior of the two nitrogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…NMR and crystallographic studies of compounds 173 confirmed the trans,trans relative configuration of the C-and N-substituents with the nitrogen atoms exhibiting as ubstantial sp 3 -character.T he prepared compound library possessede xcellent shape diversity and three-dimensionality compared to conventionald atabases, as determined by the analysis of principal moments of inertia. [67] 3. Summary and Outlook…”
Section: Non-benzofused Heterocyclesmentioning
confidence: 99%
“…NMR and crystallographic studies of compounds 173 confirmed the trans,trans relative configuration of the C-and N-substituents with the nitrogen atoms exhibiting as ubstantial sp 3 -character.T he prepared compound library possessede xcellent shape diversity and three-dimensionality compared to conventionald atabases, as determined by the analysis of principal moments of inertia. [67] 3. Summary and Outlook…”
Section: Non-benzofused Heterocyclesmentioning
confidence: 99%
“…When interfaced with transition metal complexes, the dynamic cage conveys a stereochemical preference to the chiral-at-metal 41,42 centre. Controllable and adaptable sp -carbon stereochemistry of this kind can be exploited in enantioselective synthesis 7,9,10,28,38,47,48 and chiral functional materials. 49…”
Section: Discussionmentioning
confidence: 99%
“…For example, of the 22 proteinogenic amino acids are formed solely from sp 2 -or sp 3 -hybridized carbon, nitrogen, and oxygen atoms, capped by hydrogen substituents. Of this small array of elemental building blocks, it is tetrahedral sp 3 -carbon [1][2][3][4] and sp 3 -nitrogen [5][6][7][8][9][10] atoms that have the potential to form stereogenic centres, creating chiral structures.…”
mentioning
confidence: 99%
See 2 more Smart Citations